Research into a timetable forming tool for final classes - PupeikienÄ—, Lina; Rybokas, Mindaugas (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper a high-school timetable forming tool is described. Commercial products and software for this problem solving are compared. The problems of timetable forming are analyzed. A decision for initial data computing is described. A new tool for computing problems solution is described. The results of this tool are analyzed. <!–[if gte mso 9]> Normal 0 19 false false false LT X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>